Correlation Between Disequilibrium Features and Mineral Chemistry at the Miocene Trayén Niyeu Volcano, Somún Curá Plateau, Northern Patagonia, Argentina - Cordenons, Pablo Damián (2013)
The Miocene Trayén Niyeu volcano (TNV) is the largest post-plateau volcanic building at the westernmost ranges of the mainly Oligocene Somún Curá volcanic shield. The TNV is formed by a large orthopyroxenebearing basandesitic lava field of fissural characteristics, that later on develops a central strombolian dacitic-pyroclastic edifice. Most of TNV’s lavas reveal intense disequilibrium textures and microenclaves, that increase towards the top of the sequence. Three interacting paragenesis were interpreted from detailed petrography and mineral semi-quantitative chemistry, that cannot be ascribed to a single fractional crystallization trend: a) A basic paragenesis, with ~En75, chromium-rich orthopyroxene and ~An55 plagioclase phenocrysts; b) A hybrid magma paragenesis, involving ~Ab75 plagioclase, biotite, amphibole and apatite phenocrysts; and c) A highly differentiated paragenesis, composed of sanidine, biotite and quartz phenocrysts. These three paragenetic assemblages interact at different levels, producing a wide range of disequilibrium textures and geochemical scatter. Trayén Niyeu’s effusive style may be a key for the understanding of subduction-related geochemical signals at the Somún Curá magmatic event.